Kehausan Rohani sebagai Titik Temu antara Kerinduan Manusia dan Inisiatif Ilahi - Latif, Fandy Mulya; Herman, Samuel (Sekolah Tinggi Alkitab Jember, 2026)
This study aims to analyze the story of Zacchaeus in Luke 19:1–10 to identify theological principles of spiritual thirst as the meeting point between human longing and divine initiative, as well as its relevance for Society 5.0. A qualitative descriptive analytical method was employed, involving exegetical analysis of the Greek text, historical cultural study, and review of practical theology literature. The findings reveal that spiritual thirst drives active seeking, overcomes social and cultural barriers, and prepares the heart to respond to God’s orchestrated kairos moments. This study affirms that God’s grace is not constrained by social judgment, and sincere human pursuit becomes a vessel for His saving work. In the context of Society 5.0, this model offers a practical theological framework for the church to facilitate transformative spiritual encounters by integrating technology use with deep spiritual formation.